2013
DOI: 10.1080/13639080.2012.664633
|View full text |Cite
|
Sign up to set email alerts
|

Investment in Second-Chance Education for adults and income development in Sweden

Abstract: This is an accepted version of a paper published in Journal of Education and Work. This paper has been peer-reviewed but does not include the final publisher proof-corrections or journal pagination.Citation for the published paper: Nordlund, M., Stehlik, T., Strandh, M. (2012) "Investment in second-chance education for adults and income development in Sweden" Journal of Education and Work, : 1-25 URL: http://dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 13 publications
3
24
1
1
Order By: Relevance
“…At ages 30 and 43 (variables not available at age 21), social networks are measured with four questions (index range 4-24) regarding number of friends and closeness (cronbach's α age 30 = .77, age 43 = .79), and social support with six questions (index range [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] referring to material and emotional support at ages 30 and 43 (cronbach's α age 30 = .71, age 43 = .74) [26]. Higher values on the indexes correspond to stronger support and higher access to social networks, respectively.…”
Section: Social and Labour-market Resourcesmentioning
confidence: 99%
“…At ages 30 and 43 (variables not available at age 21), social networks are measured with four questions (index range 4-24) regarding number of friends and closeness (cronbach's α age 30 = .77, age 43 = .79), and social support with six questions (index range [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] referring to material and emotional support at ages 30 and 43 (cronbach's α age 30 = .71, age 43 = .74) [26]. Higher values on the indexes correspond to stronger support and higher access to social networks, respectively.…”
Section: Social and Labour-market Resourcesmentioning
confidence: 99%
“…According to the OECD (2017), lifelong learning opportunities and inclusive labour markets will be essential to ensure that workers of all educational backgrounds have the possibility of extending their working lives. Although there is evidence that attaining adult education late in life may increase older workers' employability and their motivation to postpone retirement (Fourage & Schils, 2008;Groot & van den Brink, 2000;Hagen & Nadim, 2009;Hällsten, 2012;Jacobson, LaLonde, & Sullivan, 2005a, 2005bJepsen, Troske, & Coomes, 2014;Nordlund, Stehlik, & Strandh, 2013;Picchio & Ours, 2011;Stenberg & Westerlund, 2013, 2016Wiborg, Sandven, & Skule, 2011), some studies remain unconvinced (Raemdonck, Tillema, Grip, Valcke, & Segers, 2012;Stenberg, de Luna, & Westerlund, 2012). However, few are based on high quality data, with some exceptions (Stenberg & Westerlund, 2013, 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies over the last eight years have tried to investigate the effects of formal adult learnings on employment and labour market participation using longitudinal data (see Table 1). Although the effects of upgrading seem to vary according to whether the participants acquired basic skills or a degree from upper secondary school or tertiary school, the overall effect seems to be positive (Elman & Weiss, 2014;Hällsten, 2012; Kilpi-Jakonen, Kosyakova, Stenberg, Vono de Vilhena, & Blossfeldt, 2012;Kristensen, 2012;Nordlund, Stehlik, & Strandh, 2013;Stenberg & Westerlund, 2013, 2016. Wahler, Buchholz, Jensen, and Unfried (2014) also found that adult education (especially vocational upper-secondary education) reduced the unemployment risk and increased the reemployment chances for the unemployed in Denmark, whilst de Vilhena & Gamund (2014) found no such effect in Spain.…”
Section: Returns To Formal Adult Educationmentioning
confidence: 99%